Antioxidant Activity of Mahogany Parasite Leaves (Dendrophthu pentandra (L.) Miq.) Assessed Using the DPPH (2,2-Diphenyl-1-Picrylhydrazyl) Method - Reza, Muhammad; Nurdin, Nurmalahayati; Salsabila B.S., Siti Raihan (ALCHEMY:Journal of Chemistry, 2023)
Synthetic antioxidants, such as butyl hydroxyanisole (BHA), have carcinogenic (cancer-causing) adverse effects because they can cause type I alveolar damage and damage to lung endothelial genes. The objective of this study was to use the DPPH (2,2 diphenyl-1-picrylhydrazyl) method to investigate the antioxidant activity of natural substances found in the leaves of the mahogany parasite (Dendrophthu pentandra (L.) Miq.). Extraction, chromatography, and spectrophotometry are the techniques used. Maceration in stages utilizing n-hexane, ethyl acetate, and ethanol as solvents yielded mahogany parasite leaf extract. Phytochemical screening, thin layer chromatography testing, antioxidant activity testing utilizing a Visible Spectrophotometer, and estimating the IC50 were all performed on mahogany parasite leaf extract. The phytochemical screening results revealed that the samples included four types of secondary metabolites: flavonoids, tannins, saponins, and steroids. A thin layer chromatographic test revealed four well-separated stains using n-hexane and ethyl acetate eluent in a volume ratio of 5:5, showing the Rf as the value of the four secondary metabolites mentioned above. Based on the results of the experiments, it is possible to conclude that mahogany parasite leaves have strong antioxidant activity, with an IC50 of 8.47 ppm.